Hydrodynamic and Water Quality Dispatching Simulation System in Zhongshun Dawei River Network - LIU Jin; CHEN Yechao; DING Wu; ZHANG Wei; LI Wen (Renmin Zhujiang)
The river system in the Pearl River Delta river network is complex with numerous embankments, among which the Zhongshun Dawei river system has the most complex structure and the greatest difficulty in the joint dispatching of sluices and pumps. In order to fully explore the potential of joint dispatching of water projects in controlling water quantity and quality, this paper took Zhongshun Dawei as the research object, constructed a one-dimensional hydrodynamic-water quality coupling model for Zhongshun Dawei, and simulated water quantity and quality processes within the embankment under various dispatching schemes of sluices and pumps. On this basis, a joint optimization dispatching model for sluices and pumps was established to achieve the optimal decision-making of dispatching schemes under different water diversion conditions. Finally, based on the simulation and dispatching models of water quantity and quality, a water quantity and quality dispatching simulation system for the Zhongshun Dawei river network was developed, which realized the simulation of hydrodynamic characteristics of Zhongshun Dawei, the dynamic simulation of pollutant concentration and water quality changes, the emergency dispatching of water pollution, and the visualization of the process. A water quantity and quality simulation and control technology system based on joint optimization dispatching of sluices and pumps under the connection of the Zhongshun Dawei river system was formed. Based on the system, two typical scenarios were analyzed, and the results show that in the case of optimization dispatching, the weighted concentrations of COD and NH3-N at the end of the dispatching period are improved by 10.26% and 27.27%, respectively, compared with the case without optimization dispatching. These findings demonstrate the significant dispatching effects and provide reliable technical support for water quantity and quality dispatching decision-making in the Zhongshun Dawei region.